Teachers' experiences in sekolah penggerak program: a retrospective case study - Vebrianto, Rian; Hermita, Neni; Irawan, Dedi; Mujtahid, Iqbal Miftakhul; Thahir, Musa (Journal of Education and Learning (EduLearn), 2024)
The Sekolah Penggerak program is one of the Indonesian Government's efforts to realize the vision of Indonesian education, namely an advanced Indonesia that is sovereign, independent, and possesses the Pancasila personality. As the leading actors in education, teachers play an important role in implementing educational programs. This study was carried out to examine the experiences of teachers involved in the Sekolah Penggerak program regarding the impact of implementing the program. This study is qualitative with an exploratory case study design and a retrospective approach. The participants in this study were 15 mover teachers willing to participate, selected using a purposive sampling technique. To collect data, an open-ended questionnaire, and semi-structured interviews were used. The results of the study reveal that, in general, the Sekolah Penggerak program has a positive impact on teachers, namely helping them change mindsets to be more innovative in utilizing student-focused learning, and on students, namely increasing their motivation and critical skills. The experiences after participating in the Sekolah Penggerak program also direct teachers to be involved in collaborative reflective practice of program implementation to produce teachers who are more professional so that this program runs more effectively in the future.